TSG6 affects anti cancer drug resistance and angiogenesis in 3D spheroid model of canine mammary gland tumor cells - Ga-Hyun Lim; Ju-Hyun An; Jeong-Hwa Lee; Kyoung-Won Seo; Hwa-Young Youn (Scientific Reports)
Abstract TSG6 (Tumor necrosis factor stimulated gene-6) plays a critical role in modulating the tumor microenvironment by regulating inflammation, immune responses, and extracellular matrix remodeling. Hypoxia affects tumor growth, angiogenesis, and anti-cancer drug resistance in the tumor microenvironment, and TSG6 expression is known to influence HIF-1α expression in tumor tissues. In this study, we created TSG6 knockdown spheroids of canine mammary gland tumor (MGT) cells (CIPp and CIPm) to investigate the effects of TSG6 on angiogenesis and drug resistance in the tumor microenvironment. Using a siRNA transfection system, we induced TSG6 knockdown in canine MGT cells and formed TSG6 knockdown spheroids using an ultra-low adhesion plate. Cell viability and apoptosis were assessed by treating TSG6 knockdown spheroids with doxorubicin. Angiogenesis was evaluated by forming vascularized spheroids with canine MGT and endothelial cells (ECs). TSG6 knockdown led to reduced expression of tumor growth factors and multidrug resistance genes in canine MGT cells, as well as a significant reduction in hypoxic conditions within the spheroids. When treated with doxorubicin, TSG6 knockdown spheroids exhibited decreased viability and increased apoptosis. In a vascularized TSG6 knockdown spheroid model, TSG6 knockdown significantly reduced the expression of CD31 and tube formation in canine ECs. In conclusion, we created a TSG6 knockdown spheroid model to investigate the role of TSG6 in the tumor microenvironment. TSG6 knockdown significantly reduced anti-cancer drug resistance and angiogenesis in canine MGT cells. Therefore, TSG6 could be considered a potential therapeutic target for canine MGT.